1999
DOI: 10.1046/j.1365-2346.1999.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice of epidural analgesia for labour pain: a German survey

Abstract: Epidural analgesia is one of the preferred methods of analgesia for labour. The aim of the present survey was to evaluate current practice in obstetric analgesia in departments of anaesthesia and to make a comparison with former surveys from Germany and other countries. Questionnaires on the practice of pain relief, especially epidural analgesia, during labour and delivery were sent to 1178 anaesthetic departments in Germany in the second half of 1996. Five hundred and thirty-two completed replies were receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
(41 reference statements)
0
14
0
8
Order By: Relevance
“…10 Major reasons stated by our participants as limitations in offering epidural labour analgesia are lack of anaesthetists and dependence on anaesthetists which is similar to other studies that have shown unmet need for epidural labor analgesia. 3,11,12 Turkish study has stated that there should be good interpersonal relationship between obstetricians and anaesthetists and there should be mutual respect, understanding and support from professional point of view as their combined management is required for effective labour outcome. 13,14 Our study has shown that non-pharmacological means are the least practised method of labour analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Major reasons stated by our participants as limitations in offering epidural labour analgesia are lack of anaesthetists and dependence on anaesthetists which is similar to other studies that have shown unmet need for epidural labor analgesia. 3,11,12 Turkish study has stated that there should be good interpersonal relationship between obstetricians and anaesthetists and there should be mutual respect, understanding and support from professional point of view as their combined management is required for effective labour outcome. 13,14 Our study has shown that non-pharmacological means are the least practised method of labour analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Skiriasi žinių lygis skirtingose šalyse, skiriasi ir atliekamos epidurinės analgezijos dažnis: Belgijoje -66,6 proc., Olandijoje -9,6 proc., Lenkijoje -55 proc., Vokietijoje -86,6 proc., Norvegijoje -29,5 proc., Jungtinėje Karalystėje -29,4 proc. [6,[20][21][22][23]. Tuo metu mūsų atlikto tyrimo duomenimis, net 90,4 proc.…”
Section: Rezultatų Aptarimasunclassified
“…Gesamt <500 Geburten 500-1000 Geburten >1000 Geburten pro Jahr pro Jahr pro Jahr (n=91) [19], unsere Studie erfasste mit 59% aller Geburten eine vergleichbare Zahl für die Schweiz. Die kleinen geburtshilflichen Abteilungen mit einer Geburtenrate <500 Geburten pro Jahr waren mit 60% wie auch schon 1992 am häufigsten vertreten [15].…”
Section: -H-dienst Der Anästhesie Und Eda-opiatzusatz Nach Klinikgrößeunclassified
“…Damit entsprach die Praxis der regelmäßigen Verwendung von Opiaten in der Schweiz eher derjenigen von Großbritannien mit 88% [3] als derjenigen Deutschlands mit 28,7% [19]. Damit entsprach die Praxis der regelmäßigen Verwendung von Opiaten in der Schweiz eher derjenigen von Großbritannien mit 88% [3] als derjenigen Deutschlands mit 28,7% [19].…”
Section: Analgesie Unter Der Geburtunclassified
See 1 more Smart Citation